Minute-Scale Synthesis of Nano Silicalite-1 Zeolites - Zhang, Changsheng; Chu, Shaoqi; Jiang, Jie; Zhao, Jinchong; Wen, Song; Sun, Bing; Xu, Wei (Frontiers in Chemistry, 2022)
Synthesis of zeolites in more efficient and greener methods is of great significance in both industrial and academic fields. However, the relative long time for zeolite crystallization and much consumption of water solvent make the target challengeable. Herein, a route for ultrafast synthesis of nano Silicalite-1 zeolites in 10 min with much less water consumption has been developed. Comprehensive characterizations, i.e., X-ray powder diffraction, N2 sorption, scanning electron microscope, and NMR, confirm the high quality of such obtained Silicalite-1 zeolites. In the catalytic deoxygenation of O2-containing ethylene (mixture of O2 and ethylene), these reported Silicalite-1 zeolite samples show the comparable performance with the conventional Silicalite-1 zeolites synthesized under hydrothermal conditions. This research therefore provides a new trial toward the ultrafast synthesis of zeolite materials in an environment-friendly route.